The Influence of Digitalization, Digital Competency, Self-Efficacy on Teacher Educational Performance - Afrizal, Afrizal; Indryani, Indryani; Aina, Mia (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2025)
The rapid advancement of digital technology has transformed educational practices and increased the demand for teachers’ digital competence and self-efficacy in delivering effective instruction. This study aims to examine the relationships among digitalization, digital competence, self-efficacy, and teachers’ teaching performance. A quantitative survey design was employed, involving 200 elementary school teachers in Indonesia. Data were collected through structured questionnaires and analysed using Partial Least Squares–Structural Equation Modelling (PLS-SEM) with SmartPLS to test the proposed relationships. The findings reveal that digitalization has a positive and significant effect on teachers’ digital competence. Digital competence, in turn, significantly enhances teachers’ self-efficacy, which contributes positively to teaching performance in technology-supported learning contexts. These results indicate that self-efficacy plays a mediating role in linking digital competence to teaching performance. The study underscores the importance of strengthening teachers’ digital competence and confidence through targeted professional development, adequate technological infrastructure, and institutional support. Such efforts are essential to improve instructional quality and support teachers in responding effectively to the challenges of digital transformation in education.